Cytocompatibility Properties of an Herbal Compound Solution Support In vitro Wound Healing - Zhou, Peng; Chrepa, Vanessa; Karoussis, Ioannis; Pikos, Michael A.; Kotsakis, Georgios A. (Frontiers in Physiology, 2021)
The aim of this study was to evaluate the cytocompatibility of an herbal extract compound oral rinse [StellaLife VEGA (SLife)] against relevant human cellular models of oral surgical wound healing. SL was compared to the gold standard for peri-/post-operative oral surgical use, i.e., Chlorhexidine (CHX) and to a commonly utilized essential-oil (EO) based antiseptic rinse. Fibroblasts and primary oral stem cells of the apical papilla (SCAPs) were employed to assess its comparative cytotoxicity to the active comparator antiseptic rinses and its effects on wound healing in vitro. In cytotoxicity assays, multiple timepoints were tested ranging from clinically relevant of 60-s rinsing to protracted challenge of up to 5 min, to determine dose-dependent toxicity. The SLife group consistently demonstrated minimal cytotoxicity as compared to active comparators across experimental timepoints and different cells lines. At concentrations up to 20% v/v SLife-challenged fibroblasts and SCAPs demonstrated no significant toxicity as compared to unstimulated controls (p > 0.05). When assessing wound healing, a scratch wound assay revealed significantly accelerated cell migration for SLife as compared to CHX (p < 0.05). Notably, all active comparator antiseptic rinses affected wound healing responses by significantly reducing total collagen deposition after intermittent “rinsing” intervals that simulated post-surgical oral rinsing. Nonetheless, intermittent as well as continuous challenge of cells with SLife had a positive effect in functional collagen assays. An herbal extract compound-based oral rinse was found to be cytocompatible to cells critical to oral wound healing and to promote fibroblast migration and differentiation, contrary to existing antiseptic rinses that lack selective cytotoxicity.